Fertility postponement and labor market outcomes - Massimiliano Bratti (IZA World of Labor, 2023)
The rise in the average age of women bearing their first child is a well-established demographic trend in recent decades. Postponed childbearing can have important consequences for the mothers and, at a macro level, for the country in which they live. Research has primarily focused on the effect postponing fertility has on mothers' labor market outcomes and on the total number of children a woman has in her lifetime. Most research finds that postponing the first birth raises a mother's labor force participation and wages but may have negative effects on overall fertility, especially in the absence of supportive family-friendly policies.
Keywords: J1; J2; J3; J13; J22; 330; fertility postponement; labor market outcomes; completed fertility; family-friendly policies